2021
DOI: 10.1155/2021/6662940
|View full text |Cite
|
Sign up to set email alerts
|

Dental Fluorosis according to Birth Cohort and Fluoride Markers in an Endemic Region of Colombia

Abstract: Objectives. To analyze changes in the dental fluorosis (DF) incidence according to a birth cohort and explore current exposure to DF in a case series. Methods. Repeated cross-sectional study of two periods: 2015 and 2018. Two standardized examiners registered DF using the Thylstrup-Fejerskov index in permanent teeth of children aged 7–18 years. Period and birth cohort frequencies were estimated by a generalized linear model, binomial family, and logarithmic link function. Period estimates are presented as prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This study, whose objective was to investigate the prevalence of DF and its severity, is the first carried out in the southern region of the country, in provinces with different climatic and altitude characteristics such as Azuay, Cañar and Morona Santiago, which are apparently non-fluoridated areas, so the data obtained can serve as a starting point for future research. The results show a high prevalence of DF in the three provinces evaluated, with no significant differences between them ( p > 0.05), coinciding with previous studies carried out in some Latin American cities [ 31 , 35 , 36 , 37 , 38 , 39 ] and in Ecuador [ 30 , 40 , 41 , 42 ] ( Figure 2 ). The fluoride incorporated into the organism from water sources, processed or not processed food, or by accidental ingestion, through the consumption of toothpaste, constitutes the main source for pathologies at the dental enamel level [ 43 ], with an effect variable according to the period of contact of the mineral with the tooth in its formation stage [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study, whose objective was to investigate the prevalence of DF and its severity, is the first carried out in the southern region of the country, in provinces with different climatic and altitude characteristics such as Azuay, Cañar and Morona Santiago, which are apparently non-fluoridated areas, so the data obtained can serve as a starting point for future research. The results show a high prevalence of DF in the three provinces evaluated, with no significant differences between them ( p > 0.05), coinciding with previous studies carried out in some Latin American cities [ 31 , 35 , 36 , 37 , 38 , 39 ] and in Ecuador [ 30 , 40 , 41 , 42 ] ( Figure 2 ). The fluoride incorporated into the organism from water sources, processed or not processed food, or by accidental ingestion, through the consumption of toothpaste, constitutes the main source for pathologies at the dental enamel level [ 43 ], with an effect variable according to the period of contact of the mineral with the tooth in its formation stage [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…The evaluation of the presence of pathology requires a careful protocol and the use of one of the two systems or indices to measure the severity of the pathology, the Dean index [ 36 ] or the Thylstrup and Fejeskov index (tfi) [ 45 ], whose use is validated and considered reliable in the analysis of DF, with slight differences between them limited to the analysis protocol [ 46 , 47 ]. For that reason, the use of the Dean index was required in this study, because it was considered comparable to previous studies carried out in similar Ecuadorian populations, which evidenced the high presence of mild fluorosis in the evaluated population [ 40 ], related to the consumption of food, water, tooth brushing, pharmacies’ use [ 30 ], triggering enamel defect [ 48 ] and demineralization processes associated with dental cavities when the DF increase [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence on the dental effects of topical F is widely accepted, the risk-benefit ratio of systemic exposure to F ingestion is a complex scenario, as excessive intake during tooth development can increase the risk of DF [ 34 ]. Several studies have reported an increase in the occurrence of this dental condition in both primary [ 7 , 8 , 13 ] and permanent dentitions [ 9 , 10 , 14 , 35 ]. Studies on the timing of F intake and fluorosis have focused on the most aesthetically important teeth, the maxillary central incisors [ 10 , 11 , 12 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for the maxillary central incisors that are of greatest cosmetic importance, the critical period of susceptibility to DF comprises the first 3 years of life [ 12 ]. Recent studies have shown an increase in the prevalence of DF, both in the primary [ 7 , 8 , 13 ] and in the permanent [ 9 , 10 , 14 ] dentitions. Therefore, it is extremely important to assess children’s sources of F intake individually, as total F intake impacts the development of DF [ 5 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the living environment, there is an increase in the prevalence of people who is in the plateau. These people have the habit of drinking brick tea and using coal or wood containing fluoride to make food, which leads to the spread of fluoride from the fuel into the air and its absorption by the human respiratory tract (Saldarriaga et al, 2021a). In areas with high fluoride contents in rock or soil, fluoride leaching can occur, resulting in groundwater pollution.…”
mentioning
confidence: 99%